Lethal congenital contracture syndrome (LCCS), a fetal anterior horn cell disease, is not linked to the SMA 5q locus. Issue 1 (January 1995) - Vuopala, K; Mäkelä-Bengs, P; Suomalainen, A; Herva, R; Leisti, J; Peltonen, L
Abstract : The lethal congenital contracture syndrome (LCCS) is an autosomal recessive syndrome (McKusick 253310) leading to perinatal death owing to early onset degeneration of the anterior horn motor neurones of the spinal cord. The neuropathological findings in the LCCS closely resemble those of spinal muscular atrophy (SMA). Since all the three types of SMA have been localised to the same gene locus on the long arm of chromosome 5, we analysed samples from seven families with 10 LCCS fetuses with the microsatellite markers assigned to the SMA 5q region. Linkage analyses between the SMA linked DNA markers and the disease allele in the LCCS families excluded the critical chromosomal region around the SMA locus as the critical chromosomal region for the LCCS locus.